Sistem Informasi Geografis (SIG) untuk Zonasi Daerah Bahaya Kerusakan Bangunan Akibat Gempa Bumi: Studi Kasus pada Kota Banda Aceh dan Sekitarnya - Irwansyah, Edy; S., Iqbal; Ikhsan, M.; Yoga, R. I Made Oka (ComTech: Computer, Mathematics and Engineering Applications, 2012)
This study aims to develop a geographic information system software that has the ability to develop hazard area zoning of building damage due to earthquake, especially in Banda Aceh and the surrounding areas using peak ground acceleration (PGA) value approach. Analysis and design methods are implemented in this study. The analytical method consists of two stages, namely seismic data collection period 1973 - 2011 by magnitude more than 5 on the Richter scale and the calculation of earthquake acceleration on bedrock using the attenuation function of Crouse. The design method comprises several structured stages, which are designing: data flow diagram (DFD), entity relationship diagram (ERD), menus, screens, and state transition diagrams (STD). The main conclusions of this study is that a GIS -based local zoning of earthquake hazard risk can be built and developed with calculation and classification approach of the peak ground acceleration (PGA). In addition, there is a relationship significant spatial found by comparing the results with the zoning patterns of building damage in the earthquake of 2004.